(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The topic of this study is the use of Students Team Achievement Division (STAD) technique to enhance the students’ writing creativity, an action research of the eighth grade students of SMP N 4 Pematangsiantar in the academic year 2023/2024. In this study, the writer limited the discussion by stating the following problem: How STAD technique be applied to enhance the student’s writing creativity? The objective of this study was to describe how the application of STAD teaching technique in enhance student’s writing creativity. Action research approach was adopted in this study. The population of the study was eighth grade students of SMP N 4 Pematangsiantar in the academic year of 2023/2024. The writer took the whole students of VIII-10 as the subject of the research. There were 30 students. It was conducted on 13th until 24th of April 2024. The techniques used for obtaining data were collecting data from the students by using writing test. In the first activity, the writer gave a pre-test in order to find out the student’s creativity in writing descriptive text. The second activity, the writer gave a treatment where the writer gave and explained the material of descriptive text to students. In the last activity, the students were given a post-test. The result of the students’ progress during the teaching and learning process by using Students Team Achievement Division (STAD) technique was good. The students’ achievement increased from the second meeting to the last. The students’ mean value in pre-test was 46,17 and the mean value of post-test was 74,47. The progress can be seen that most students chose to work in groups because it made them feel happy and appreciated their friend’s opinions more. Based on the result the writer concludes that the use of Students Team Achievement Division technique could be applied in enhancing students’ writing creativity